2020
DOI: 10.1152/jn.00626.2019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gain-of-function effects of the KCNMA1-N999S mutation on human BK channel properties

Abstract: KCNMA1, encoding the voltage- and calcium-activated potassium channel, has a pivotal role in brain physiology. Mutations in KCNMA1 are associated with epilepsy and/or dyskinesia (PNKD3). Two KCNMA1 mutations correlated with these phenotypes, D434G and N999S, were previously identified as producing gain-of-function (GOF) effects on BK channel activity. Three new patients have been reported harboring N999S, one carrying a second mutation, R1128W, but the effects of these mutations have not yet been reported unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 51 publications
(58 reference statements)
0
41
1
Order By: Relevance
“…Another de novo GOF variant in KCNMA1 (c.2984 A > G (p.N995S)) was recently reported in the patients from two independent families who had absence epilepsy in early childhood, but did not develop paroxysmal dyskinesia 8 . Subsequent biophysical characterization showed that N995S, similar to N536H, also specifically increases voltage sensitivity without affecting Ca 2+ ‐dependent activation 8,19 . N995 is located at the C‐terminal end of the channel and is spatially distal from N536 and the voltage sensor (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Another de novo GOF variant in KCNMA1 (c.2984 A > G (p.N995S)) was recently reported in the patients from two independent families who had absence epilepsy in early childhood, but did not develop paroxysmal dyskinesia 8 . Subsequent biophysical characterization showed that N995S, similar to N536H, also specifically increases voltage sensitivity without affecting Ca 2+ ‐dependent activation 8,19 . N995 is located at the C‐terminal end of the channel and is spatially distal from N536 and the voltage sensor (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…[1][2][3] We describe 3 unrelated patients with cataplexy, all sharing the same KCNMA1 gene mutation identified by whole exome sequencing (KCNMA1 [NM_002247.3] c.2984 A > G [p.N999S]), previously described as conferring a gain of function and reported in patients with paroxysmal dyskinesia and developmental delay phenotype. [1][2][3][4] Parents do not harbor the mutation and are asymptomatic. Patient 1 has an additional variant in the KCNMA1 gene (c.3382 C > T [p.Arg1128Trp]) predicted to be benign.…”
mentioning
confidence: 99%
“…Patient 1 has an additional variant in the KCNMA1 gene (c.3382 C > T [p.Arg1128Trp]) predicted to be benign. 4 Patient 1 is a 4-year-old female with cataplexy (Video S1), hypotonia, and global developmental delay, conceived via sperm donor (neither KCNMA1 variant is maternally inherited, father's genotype is unknown). MRI brain was normal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dyskinetic attacks emerge in early infancy or childhood, are frequently co-morbid with absence or generalized tonic-clonic seizures 3 , and in some cases occur alongside developmental delay 4 . PNKD3 is caused by dominant gain-of-function (GOF) mutations in KCNMA1, encoding the pore forming αsubunit of the hSlo1 BK (big K + conductance) channel [3][4][5][6][7] . BK channels are voltage-and Ca 2+activated potassium channels, and modulate synaptic output from excitable cells by gating K + efflux during the repolarization and afterhyperpolarization (AHP) phases of the action potential (AP) [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%